Examples of Conflicted Narrators in the Book Tahdheeb Al-Tahdheeb by Al-Hafiz Ibn Hajar: A Comparative Study - Jassim, Khansa Nazem; Saleh, Abdul Sattar Ibrahim (Journal of Posthumanism, 2025)
Linguistically, confliction refers to three things: difference, imbalance, and movement. A tradition is not considered conflicted unless the two narrations are equally valid, but it is impossible to reconcile or give preference to one over the other. Confliction in a narrator indicates weakness, signifying that the narrator did not perfectly memorize the tradition. It can occur in the chain of transmission and the content, though it is more common in the chain than in the content. Rarely do narrators judge the content as conflicted without referencing the chain of transmission. Confliction among narrators has many causes, including lack of precision, illusion, poor memorization, and others. This study seeks to clarify the reasons for the imams' judgments on certain narrators as conflicted, focusing on three specific narrators.